Penyuluhan Fisioterapi K3 dan Ergonomi: Edukasi Pentingnya Posisi Kerja Yang Ergonomis dan Self Exercise untuk Mengurangi Keluhan Nyeri Punggung Bawah pada Guru - Merianti, Nisfah; Atika Yulianti (Rena Cipta Mandiri, 2025)
Background: Low back pain (LBP) management involves both pharmacological and non-pharmacological approaches. One solution to prevent and manage LBP is through workplace interventions. Job demands are often linked to some of the main causes of occupational diseases, such as repetitive physical tasks, improper posture, and stress from uncomfortable standing positions, all of which occur while working. Objective: To enable participants to recognize ergonomic work positions and self exercise that can be done independently at work and at home. Methods: The method given was counseling to teachers and teaching staff in the form of health promotion about the introduction of the physiotherapy profession, Low Back Pain (LBP) conditions, a brief description of ergonomics, ergonomic aspects, good and correct ergonomics and self exercise at work and at home using power point media (PPT) and leaflets by conducting pre-post tests to measure the level of knowledge. Conclusion: From the volleyball sports community physiotherapy activities carried out on March 18, 2025 at SDN 001 Merancang Ilir showed significant results in increasing knowledge. This increase shows the effectiveness of the counseling conducted in providing a better understanding of injury prevention practices.